Elevated IL-6 and CRP Levels Are Associated With Incident Self-Reported Major Mobility Disability: A Pooled Analysis of Older Adults With Slow Gait Speed. (5th April 2021) - Beavers, Daniel P; Kritchevsky, Stephen B; Gill, Thomas M; Ambrosius, Walter T; Anton, Stephen D; Fielding, Roger A; King, Abby C; Rejeski, W Jack; Lovato, Laura; McDermott, Mary M; Newman, Anne B; Pahor, Marco; et al.
Abstract: Background: Elevated interleukine-6 (IL-6) and C-reactive protein (CRP) are associated with aging-related reductions in physical function, but little is known about their independent and combined relationships with major mobility disability (MMD), defined as the self-reported inability to walk a quarter mile. Methods: We estimated the absolute and relative effect of elevated baseline IL-6, CRP, and their combination on self-reported MMD risk among older adults (≥68 years; 59% female) with slow gait speed (<1.0 m/s). Participants were MMD-free at baseline. IL-6 and CRP were assessed using a central laboratory. The study combined a cohort of community-dwelling high-functioning older adults (Health ABC) with 2 trials of low-functioning adults at risk of MMD (LIFE-P, LIFE). Analyses utilized Poisson regression for absolute MMD incidence and proportional hazards models for relative risk. Results: We found higher MMD risk per unit increase in log IL-6 (hazard ratio [HR] = 1.26; 95% confidence interval [95% CI] 1.13–1.41). IL-6 meeting predetermined threshold considered to be high (>2.5 pg/mL) was similarly associated with higher risk of MMD (HR = 1.31; 95% CI 1.12–1.54). Elevated CRP (CRP >3.0 mg/L) was also associated with increased MMD risk (HR = 1.38; 95% CI 1.10–1.74). The CRP effect was more pronounced among participants with elevated IL-6 (HR = 1.62; 95% CI 1.12–2.33) compared to lower IL-6 levels (HR = 1.19; 95% CI 0.85–1.66). Conclusions: High baseline IL-6 and CRP were associated with an increased risk of MMD among older adults with slow gait speed. A combined biomarker model suggests CRP was associated with MMD when IL-6 was elevated.